2022
DOI: 10.1038/s41467-022-32985-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of venous or capillary blood-derived SARS-CoV-2-specific T cell response determines COVID-19 immunity

Abstract: T cells specific for SARS-CoV-2 are thought to protect against infection and development of COVID-19, but direct evidence for this is lacking. Here, we associated whole-blood-based measurement of SARS-CoV-2-specific interferon-γ-positive T cell responses with positive COVID-19 diagnostic (PCR and/or lateral flow) test results up to 6 months post-blood sampling. Amongst 148 participants donating venous blood samples, SARS-CoV-2-specific T cell response magnitude is significantly greater in those who remain prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…Limitation in blood volume obtained from adolescents precluded us from detecting small differences in some outcomes between adults and adolescents, yet most of our outcomes tested satisfied non-inferiority testing, demonstrating that diverse immune responses in adults and adolescents were not different by a clinically significant margin. Because of the critical roles of T helper (Th) 1 in virus controlling 42 and the limitation of blood volume obtained from adolescents, we focused our efforts on quantifying post-vaccine Th1 T cell responses. Previously, in an adult vaccine study, we found that Spike-specific IL-4 + Th2 responses are not boosted by two-dose BNT162b2 vaccination, and the majority of post-vaccine responses were IFN-γ + T effector memory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Limitation in blood volume obtained from adolescents precluded us from detecting small differences in some outcomes between adults and adolescents, yet most of our outcomes tested satisfied non-inferiority testing, demonstrating that diverse immune responses in adults and adolescents were not different by a clinically significant margin. Because of the critical roles of T helper (Th) 1 in virus controlling 42 and the limitation of blood volume obtained from adolescents, we focused our efforts on quantifying post-vaccine Th1 T cell responses. Previously, in an adult vaccine study, we found that Spike-specific IL-4 + Th2 responses are not boosted by two-dose BNT162b2 vaccination, and the majority of post-vaccine responses were IFN-γ + T effector memory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum cytokine levels are associated with severe COVID-19 infections and are a strong predictor of adverse disease outcomes 19 . Adaptive immune responses, including the development of a coordinated SARS-CoV-2-specific CD4 + and CD8 + T cell response and neutralizing antibodies, are associated with a reduction in COVID-19 disease severity 20 22 ; however, certain T cell responses including unconventional CD16 + T cells 23 , mucosal-associated invariant T (MAIT) cells 24 and γδ T cells 25 may be increased in severe COVID-19 and are potentially related to immunopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Despite such evidence, epidemiological assessments of the prevalence of SARS-CoV-2 have mainly utilized serologic assays since antibodies are easier to measure than T cells responses. However, methodologies to rapidly detect virus-specific T cell responses flourished during the COVID-19 pandemic 21,[35][36][37] , including the use of whole blood which appeared to correlate with protection from SARS-CoV-2 infection in one study 37 . Here, we show directly that cytokine detection following whole blood stimulation with peptides can be implemented in locations within a few hours distance from a facility with biosafety level-1 cabinets.…”
Section: Discussionmentioning
confidence: 99%